A normative model for deliberative constitution-building - Jordi Pacheco i Canals (Revista Catalana de Dret Públic, 2019)
Constitution-making in Western Europe has shifted from the traditional post-war model and taken a deliberative turn, seeking full democratic legitimation, though most constitutional initiatives incorporating ordinary citizens have not been fully successful. To overcome this lack of efficiency, this article offers a normative model for deliberative constitution-building. The model formulates citizens deliberating systematically and massively in minipublics with formal institutions, epistemocracy, political parties, officials, and mass communication. It also transforms most of the normative ideals to those that can be regulated only by legal norms, avoiding dependence on citizens’ ethical behavior. Only a few of them remain as recommendations for political consensus before starting constitutional change. The first part of the article describes general issues related to constitution-building from a deliberative perspective, such as the strengths and weaknesses of minipublics, political commitment before starting, and the scope of the future constitution. The second one describes its practical deployment and the role of each actor such as the parliament or constituent assembly, political parties, scientific and monitoring committees, the executive operator, participants, and general public; the design of the deliberative system and how to frame the debate; massive deliberation in equatable minipublics and their link with politicians, public opinion, and representative institutions; and, finally their connection to posterior constitutional decision-making phases through accountability.